2017
DOI: 10.1002/cphc.201700450
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Internal Dynamics Probed in Nanodiscs

Abstract: Nanodiscs offer a very promising tool to incorporate membrane proteins into native‐like lipid bilayers and an alternative to liposomes to maintain protein functions and protein–lipid interactions in a soluble nanoscale object. The activity of the incorporated membrane protein appears to be correlated to its dynamics in the lipid bilayer and by protein–lipid interactions. These two parameters depend on the lipid internal dynamics surrounded by the lipid‐encircling discoidal scaffold protein that might differ fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 50 publications
(77 reference statements)
10
55
0
Order By: Relevance
“…1). These experiments were performed at 10 • C, and based on results from previous NMR experiments on nanodiscs (Martinez et al, 2017) as well as a melting temperature ≈ 24 • C for DMPC, we expect the lipids to be in the gel-phase. Our SAXS and SANS data all exhibit a flat Guinier region at low and indicate no signs of aggregation ( Fig.…”
Section: Sansmentioning
confidence: 99%
See 2 more Smart Citations
“…1). These experiments were performed at 10 • C, and based on results from previous NMR experiments on nanodiscs (Martinez et al, 2017) as well as a melting temperature ≈ 24 • C for DMPC, we expect the lipids to be in the gel-phase. Our SAXS and SANS data all exhibit a flat Guinier region at low and indicate no signs of aggregation ( Fig.…”
Section: Sansmentioning
confidence: 99%
“…We continued to investigate the impact of temperature and the presence of the His-tags on both the SAXS measurements and the resulting geometrical model of ΔH5-DMPC. We acquired standard solution SAXS data for a new preparation of the ΔH5-DMPC nanodiscs, this time without His-tags and measured at both 10 • C and 30 • C. At these two temperatures the DMPC is expected to be dominantly in the gel and liquid phase, respectively, as they are below and above the melting transition temperature (Martinez et al, 2017) (see also DSC analysis below). We used a standard solution SAXS setup for these measurements, as this at present provides a better control of both the sample temperature and sample concentration than in the SEC-SAXS based measurement.…”
Section: Temperature Dependence Probed By Saxs and Sansmentioning
confidence: 99%
See 1 more Smart Citation
“…2A), [58]. However, their partially denaturing properties, high degree of curvature and unnatural lateral pressure profile may introduce perturbances of MP structure, function and dynamics [45,[59][60][61][62]. Therefore, alternative membrane mimetics have been developed to embed the protein in a flat lipid bilayer, such as bicelles, which are composed of a detergent/lipid pair [63].…”
Section: Choice Of Membrane Mimetics and Caveats With Detergentsmentioning
confidence: 99%
“…Nanodiscs are derived from apolipoprotein A1, also called membrane scaffolding protein (MSP), an amphipathic protein in which the hydrophobic helices interact with the acyl chains of the lipids while the hydrophilic sides are exposed to the solvent, thus allowing the formation of a lipid bilayer patch in solution. However, it was recently reported that the nanodisc lipid internal dynamics and thermotropism may be substantially altered, abolishing gel-fluid phase transitions and increasing site-specific order parameters that can only be fine-tuned with the addition of cholesterol [15]. As it is known that P-gp reshapes the surrounding lipid environment up to a radius of 15-20 nm [16], and as the inferred nanodisc size is ~10 nm (containing 120-160 lipids) [15], under the temperature conditions required by cryo-EM and using relatively small nanodiscs, the protein conformational space may be perturbed.…”
mentioning
confidence: 99%